A qualitative research analysis of gender-based parities and disparities at work place experienced by female dentists of Vadodara, India - Ramya R Iyer; Rajesh Sethuraman; Medha Wadhwa (Wolters Kluwer Medknow Publications, 2020)
Aim: To assess the gender-based parities and disparities at work place experienced by female dentists of Vadodara, India. Materials and Methods: In-depth face-to-face qualitative semi-structured interviews in English were conducted among 12 female dentists of Vadodara. Female dentists working with one/more male colleague or auxiliary were selected through purposive sampling. Interviews were conducted as per Kvale's principles and recorded using a digital voice recorder. Transcribed data was analyzed using Giorgi's phenomenological analysis. Results: The recurring themes identified were: (a) Striking work-family balance (b) Dependence on male authority for instating work discipline (c) Male dentists' hostility to "woman in power" concept (d) Male dentists' superiority in technical skills (e) privileges for women dentists. Conclusions: There is a need to improve the work environment of women dentists. Social support, sensitivity among male colleagues, and generous institutional policies will enable increased contribution from women to the profession.